KONFLIK PERAN GANDA TERHADAP STRES KERJA KARYAWAN WANITA YANG SUDAH MENIKAH DI PT X - Tri Hetyta br Sinulingga; Sutarto Wijono (Jurnal Cakrawala Ilmiah, 2023)
the purpose of this study was to determine the influence of dual role conflict on work stress among married women employees in PT X. This study method used 74 married women employees as a sample out of 280 population with random sampling technique. The used measuring instrument was modified from Carlson, Kacmar, and Wilson in 2000, namely work family conflict and Cici Trayodika in 2022 namely work stress. The analysis of simple linear data, the results of the analysis show R2 = 33,833; P<0,05, which is that there is a significant influence of dual conflict role on work stress in married women employees at PT X.